STRATEGI PENGEMBANGAN USAHA KAKAO PADA KOPERASI EIBER SUTH COKRAN RANSIKI KABUPATEN MANOKWARI SELATAN - Mayawati, Deasi; Julia Inchia Sand; Kunto Wibowo (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2024)
The Ebier Suth Cokran Cooperative is a cooperative that produces Ransiki cocoa and markets it in the form of dry cocoa beans for domestic and foreign markets. In running the cocoa production business, the cooperative forms partnerships with cocoa farmers in South Manokwari district. This research aims to determine the internal and external factors in the cocoa business at the Eiber Suth Cokran Cooperative and to determine the business development strategy at the Eiber Suth Cokran Ransiki Cooperative, South Manokwari Regency. The method used in this research is the descriptive method. The data analysis used in this research uses SWOT analysis. The research results show that from the evaluation results of the Internal Factor Strategy Analysis (IFAS) matrix, the strength and weakness factors have a score of 3.35, which identifies that the Eiber Suth Cokran Cooperative is internally strong, whereas in terms of internal strength, it is in the product and management aspects. Meanwhile, the External Factor Analysis Strategy Matrix (EFAS) shows that the opportunity and threat factors have a score of 2.18, which identifies that the Eiber Suth Cokran Cooperative takes advantage of existing opportunities by avoiding threats. The business development strategy that can be implemented by the Eiber Suth Cokran Cooperative is StrengthsOpportunities (SO) to maintain quality cocoa bean products that are always available. WeaknessesOpportunities (WO): improving technology to maintain the superiority of cocoa beans. Strength-Threat (ST): increasing production and quality from processing to post-harvest handling and sorting of cocoa beans in order to maintain good-quality cocoa beans. Weaknesses-Threats (WT): optimizing cocoa plants by fertilizing and dealing with pests and diseases of cocoa plants